Successful Treatment of Cryoglobulinaemia with Rituximab - Choudhry, M. (S. Karger AG, 2012)
Cryoglobulinaemia is a systemic inflammatory condition characterised by immune complex-mediated small-to-medium-sized vasculitis. It has a wide variety of presentations ranging from bruising, neuropathy, and hepatosplenomegaly to acute renal failure. Mixed cryoglobulinaemia is the most common type and is strongly associated with hepatitis C. Management approaches include use of cyclophosphamide, prednisolone, and plasmapheresis, with differing views on alternative treatments in resistant cases. Rituximab has emerged as an attractive option in resistant cases on account of its potent immunosuppressive effects on B cells. We describe a case of type 2 mixed cryoglobulinaemia in association with non-Hodgkin's lymphoma resistant to standard treatments which responded well to rituximab. This case is remarkable as mixed cryoglobulinaemia associated with non-Hodgkin's lymphoma presenting with nephritis is unusual, and, contrary to the high rate of recurrence in lymphoma-related cryoglobulinaemia, our patient has not shown any recurrence over 24 months. This highlights an alternative treatment modality which can be used in patients not responsive to existing managements for this condition with benefits of minimal side effects and no oncogenetic potential.